(untitled) (Research, Society and Development, 2022)
Introduction: Assessing the stability of products before marketing them is of great importance. Cosmetics that present problems in organoleptic, physicochemical and microbiological stability are failing to comply with basic quality requirements and can pose risks to consumer health. Objective: To evaluate the stability of a whitening formulation developed and manipulated in a pharmacy in Cascavel - PR as a function of time. Methodology: Evaluation of the formation through preliminary stability and accelerated stability studies, based on centrifugation tests, thermal stress, ice/thaw cycle. During the tests the organoleptic and physicochemical characteristics were evaluated. The tests were carried out according to the methodology proposed by Anvisa. Results: The formulation remained unchanged after centrifugation. In the thermal stress test, changes were observed in viscosity from 40ºC and changes in color and odor after 50ºC. In the ice/thaw cycle, the organoleptic characteristics changed from time 7 onwards and were more evident at time 21. The pH value changed in all tests performed. Conclusion: Taking into account the stability analyzes carried out, it can be observed that the whitening formulation does not have stability. C and that the pharmacy put a warning label to keep the product sheltered away from heat to avoid possible changes in it, and that further studies should be carried out in order to determine the validity of the formulation.